Evaluation of F1 Hybrids in Snakegourd - Sudevkumar V (Department of Olericulture, College of Horticulture, 1995)
An investigation on “Evaluation of F1 hybrids in Snakegourd” was conducted at College of Horticulture, Kerala Agricultural University, Vellanikkara, during 1992 – 1994. Ten F1 hybrids were evaluated along with their parents and a standard check variety TA – 19 for two seasons. Heterosis was estimated in different seasons for different characters like days to first male flower anthesis, days to first female flower opening, days to first fruit picking maturity, number of fruits per plant, average fruit weight, yield per plant, fruit length, fruit girth, flesh thickness, number of seeds per fruit, hundred seed weight, seed weight/fruit, total crop duration, fruit fly incidence, crude fibre content of fruit, crude protein content of fruit and ash content of fruit. The heterotic behaviour of all the ten hybrids was studied for season 1, season 11 and pooled over seasons for each character. Heterosis was estimated in terms of relative heterosis, heterobeltiosis and standard beterosis. Cost of production of F1 seeds of snakegourd was also worked out. All the ten hybrids recorded significant heterosis in terms of relative heterosis, heterobeltiosis and standard heterosis for characters like days to first male flower opening, days to first female flower opening, days to first fruit picking maturity, number of fruits/plant and total yield/plant in both the seasons. The number of days taken for flower opening, fruit picking maturity as well as the total crop duration were found to be lower in second season (summer). Seasonal variation was significant in number of days taken to first fruit picking maturity, total yield, number of seeds/fruit, seed weight/fruit and total crop duration. The hybrids which exhibited high heterosis for yield in terms of relative heterosis, heterobeltiosis and standard heterosis were P4 x P3 (146.05%, 128.03% and 71.00% respectively), DFH 15 x DfH 58 (124.27%, 124.24% and 67.36% respectively) and P13 x P4 (113.10%, 110.83% and 61.57% respectively). The per se performance for yield was high for P4 x P3 (13.02 kg), DFH 15 x DFH 58 (12.75 kg), P13 x P4 (12.31 kg) and P9 x P5 (12.24 kg). Earliness for 6-8 days was also manifested by P4 x P3, DFH 15 x DFH 58 and P9 x p5. The time taken for production of one kg of F1 hybrid seed was 10.29 hours for preparatory operations and crossing work and the cost incurred was Rs. 103/kg of seed.